Mindfulness and Foreign Language Anxiety in the Bilingual Primary Classroom - Mortimore, Louisa (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2017)
Pilot study of how the use of mindfulness techniques may positively affect foreign language anxiety in bilingual primary classrooms. Data collection used qualitative and quantitative measures: self-reporting questionnaires to measure mindfulness (CAMM) and attitude to L2, language tests to determine the rate of improvement in language learning, and teacher observation. Attention and disturbance was logged in each session. While results are inconclusive, a modest improvement in the L2 was recorded in the test group which had high attention and low disturbance scores.